2019
DOI: 10.1111/bjd.17820
|View full text |Cite
|
Sign up to set email alerts
|

LEKTI domains D6, D7 and D8+9 serve as substrates for transglutaminase 1: implications for targeted therapy of Netherton syndrome

Abstract: Background Transglutaminase (TG)1 plays a key role in the formation of the cornified envelope and thus in the maintenance of the epidermal barrier. Patients with Netherton syndrome (LEKTI deficiency) have increased activity of both TG1 and serin proteases. Objectives To determine whether there is a functional biochemical link between TG1 and LEKTI and whether LEKTI domains could possibly serve as substrates for TG1. Methods We analysed the protein sequence of LEKTI for possible TG1 recognition sites using bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Other crucial genes for epidermal barrier function are TGM1 and SPINK5. It has been found that LEKTI serves as TGase-1 substrate and patients with Netherton syndrome have increased activity of both TGase-1 and serine proteases (Wiegmann et al, 2019). Similarly, we observed elevated expression of TGase-1 in SPINK5-siRNA treated 3D skin constructs.…”
Section: Role Of Sdr9c7 In Comparison To Other Genes In Epidermal Barsupporting
confidence: 80%
“…Other crucial genes for epidermal barrier function are TGM1 and SPINK5. It has been found that LEKTI serves as TGase-1 substrate and patients with Netherton syndrome have increased activity of both TGase-1 and serine proteases (Wiegmann et al, 2019). Similarly, we observed elevated expression of TGase-1 in SPINK5-siRNA treated 3D skin constructs.…”
Section: Role Of Sdr9c7 In Comparison To Other Genes In Epidermal Barsupporting
confidence: 80%
“…Under certain conditions, more than one abnormal finding is present. Examples include abnormal lipid composition of the SC associated with impaired epidermal calcium gradients in KID syndrome [14,15], altered calcium gradients accompanied by increased skin pH and CE rearrangement in aging skin [16], loss-of-function mutations in filaggrin in atopic dermatitis [28], and increased activity of TG1 and serine proteases in Netherton syndrome [61]. These accompanying findings could provide a direction for future research to identify more organized mechanism involved in barrier dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…These findings emphasize that corneodesmosome degradation depends on the sum of protease and inhibitor activities. In addition to increased activity of serine proteases, TGase1 activity has been reported to increase in Netherton syndrome, which contributes to the novel functional link between LEKTI and TGase1 [61]. Considering that impaired corneodesmosome degradation can lead to hyperkeratosis as a clinical symptom, hyperkeratosis is not considered as a cause of barrier dysfunction related to desquamation.…”
Section: Desquamationmentioning
confidence: 99%
“…LEKTI, the protein product of the SPINK5 gene, is cleaved by furin into specific domains, with some of these domains undergoing further activation by the epidermal enzyme transglutaminase 1. [ 49 ] These activated subunits of LEKTI then inhibit the activation of KLK5, KLK6, KLK7 and KLK14, thus inhibiting corneodesmosome breakdown and desquamation and inhibiting the pro‐inflammatory effects of KLK6. [ 20,50 ] This is consistent with absence or splitting of the cornified layer sometimes seen in NS, [ 26 ] in which dysfunction of LEKTI leads to uninhibited breakdown of corneodesmosomes.…”
Section: Lekti and Matriptase Have Opposing Functions In Cutaneous Pr...mentioning
confidence: 99%